Tenebrio molitor Spätzle 1b Is Required to Confer Antibacterial Defense Against Gram-Negative Bacteria by Regulation of Antimicrobial Peptides - Bae, Young Min; Jo, Yong Hun; Patnaik, Bharat Bhusan; Kim, Bo Bae; Park, Ki Beom; Edosa, Tariku Tesfaye; Keshavarz, Maryam; Kojour, Maryam Ali Mohammadie; Lee, Yong Seok; Han, Yeon Soo (Frontiers in Physiology, 2021)
Innate immunity is the ultimate line of defense against invading pathogens in insects. Unlike in the mammalian model, in the insect model, invading pathogens are recognized by extracellular receptors, which activate the Toll signaling pathway through an extracellular serine protease cascade. In the Toll-NF-κB pathway, the extracellular spätzle protein acts as a downstream ligand for Toll receptors in insects. In this study, we identified a novel Spätzle isoform (TmSpz1b) from RNA sequencing database of Tenebrio molitor. TmSpz1b was bioinformatically analyzed, and functionally characterized the antimicrobial function by RNA interference (RNAi). The 702 bp open reading frame of TmSpz1b encoded a putative protein of 233 amino acid residues. A conserved cystine-knot domain with seven cysteine residues in TmSpz1b was involved in three disulfide bridges and the formation of a spätzle dimer. TmSpz1b was mostly expressed in the hemocytes of T. molitor late instar larvae. The mRNA expression of TmSpz1b was highly induced in the hemocytes after Escherichia coli, Staphylococcus aureus, and Candida albicans stimulation of T. molitor larvae. TmSpz1b silenced larvae were significantly more susceptible to E. coli infection. In addition, RNAi-based functional assay characterized TmSpz1b to be involved in the positive regulation of antimicrobial peptide genes in hemocytes and fat bodies. Further, the TmDorX2 transcripts were downregulated in TmSpz1b silenced individuals upon E. coli challenge suggesting the relationship to Toll signaling pathway. These results indicate that TmSpz1b is involved in the T. molitor innate immunity, causes the sequestration of Gram-negative bacteria by the regulatory action of antimicrobial peptides, and enhances the survival of T. molitor larvae.